Opportunities for quality improvement in the morbidity pattern of older adults undergoing pulmonary lobectomy for cancer. Issue 3 (April 2021) - De León, Luis E.; Rochefort, Matthew M.; Bravo-Iñiguez, Carlos E.; Fox, Sam W.; Tarascio, Jeffrey N.; Cardin, Kristin; DuMontier, Clark; Frain, Laura N.; Jaklitsch, Michael T.
Abstract: Background: There is limited information on the frequency of complications among older adults after oncological thoracic surgery in the modern era. We hypothesized that morbidity and mortality in older adults with lung cancer undergoing lobectomy is low and different than that of younger patients undergoing thoracic surgery. Methods: All patients undergoing lobectomy at a large volume academic center between May 2016 and May 2019 were included. Patients were prospectively monitored to grade postoperative morbidity by organ system, based on the Clavien-Dindo classification. Patients were divided into two groups: Group 1 included patients 65–91 years of age, and Group 2 included those <65 years. Results: Of 680 lobectomies in 673 patients, 414(61%) were older than 65 years of age (group 1). Median age at surgery was 68 years (20–91). Median hospital stay was 4 days (1–38) and longer in older adults. Older adults experienced higher rates of grade II and IV complications, mostly driven by an increased incidence of delirium, atrial fibrillation, prolonged air leak, respiratory failure and urinary retention. In this modern cohort, there was only 1 stroke (0.1%), and delirium was reduced to 7%. Patients undergoing minimally invasive (MI) surgery had a lower rate of Grade IV life-threatening complications. Older adults were more likely to be discharged to a rehabilitation facility, however this difference also disappeared with MI surgical procedures. Conclusions: Current morbidity of older adults undergoing lobectomy for cancer is low and is different than that of younger patients. Thoracotomy may be associated with postoperative complications in these patients. Our findings suggest the need to consider MI approaches and broad-based, geriatric-focused perioperative management of older adults undergoing lobectomy.